Management of severe bronchiolitis: impact of NICE guidelines. Issue 5 (24th November 2018) - Griffiths, Benedict; Riphagen, Shelley; Lillie, Jon
Abstract : Objective: To understand the impact of the National Institute for Health and Care Excellence (NICE) bronchiolitis guidelines on the management of children referred to paediatric intensive care unit (PICU) with bronchiolitis. Design and setting: Data were collected on all children referred to a regional PICU transport service with the clinical diagnosis of bronchiolitis during the winter prior to the NICE consultation period (2011–2012) and during the winter after publication (2015–2016). Management initiated by the referring hospital was assessed. Results: There were 165 infants referred with bronchiolitis in epoch 1 and 187 in epoch 2. Nebuliser use increased from 28% in epoch 1 to 53% in epoch 2. Increased use of high-flow nasal cannula oxygen and reduction in continuous positive airway pressure use were observed. The use of antibiotics did not change between epochs. Conclusion: The use of nebulised therapies has increased in the management of severe bronchiolitis despite national guidance to the contrary.